UNDETECTED HEARING LOSS IMPACTS LANGUAGE DEVELOPMENT AND ACADEMIC ACHIEVEMENT OF INDONESIAN CHILDREN - Cleghorn, Duane William (English Education Department of STKIP Pasundan, 2023)
The purpose of this research is to generate a greater awareness of mild hearing loss (MHL) and to expose its negative impact on the language development and academic success of Indonesian children. The research also seeks for practical solutions to reduce the impact of MHL. Three goals are to discover: 1) the causes and extent of MHL, 2) the extent of teacher awareness of MHL, and 3) the influence of the classroom environment on the learning process of MHL students. The first objective is achieved via a systematic literature review (SLR). The second objective is achieved through two surveys created in Google Forms. Survey I targets active teachers in primary, middle, and secondary schools. Survey II targets prospective teachers in their eighth semester of training. The third objective is achieved by observing the classroom environment and teaching strategies of teachers. Findings: 1) The percentage of students with MHL is much higher than teachers estimate. 2) Teachers are not sufficiently aware of the extent and effects of MHL. 3) The classroom environment and teaching strategies can be made more favorable for MHL students. Conclusion: Greater awareness of MHL can generate changes that benefit Indonesian children who have MHL.